2021
DOI: 10.1111/jonm.13504
|View full text |Cite
|
Sign up to set email alerts
|

Kirkpatrick's evaluation of the effect of a nursing innovation team training for clinical nurses

Abstract: Aim: This study aims to design a 100-h training programme for nursing innovation teams and to evaluate the effect of this training programme using Kirkpatrick's model. Background:The innovative capability of nurses is a powerful driver for the development of the nursing discipline, and it is currently at a low to medium level in China. Innovation competency development has become a research trend in nurses' inservice education, but only changes in nursing innovation behaviours before and after training have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…He et al (2019) revealed that charismatic leadership is positively related to group innovation behavior in the context of Chinese firms. Similarly, Huang et al (2022) asserted on the latter findings and explained that charismatic leadership has a positive effect on innovation behavior in the context of the Chinese hospitality industry. These findings suggest that the relationship between charismatic leadership and group innovation behavior may be context-dependent and may vary across different cultural and organizational settings (Rezaei et al , 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 89%
“…He et al (2019) revealed that charismatic leadership is positively related to group innovation behavior in the context of Chinese firms. Similarly, Huang et al (2022) asserted on the latter findings and explained that charismatic leadership has a positive effect on innovation behavior in the context of the Chinese hospitality industry. These findings suggest that the relationship between charismatic leadership and group innovation behavior may be context-dependent and may vary across different cultural and organizational settings (Rezaei et al , 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 89%
“…Therefore, it is recommended that nursing managers also pay attention to the development of innovative behaviours among nurses during the pandemic. By conducting online academic meetings, a blended emergent research training programme (Chen et al, 2022) or nursing innovation training (Huang et al, 2021) and adopting performance incentive mechanisms to encourage nurses to actively join scientific research projects, it helps to bring into play nurses' self-potential and learning initiative and promotes nurses' innovative behaviours, thus meeting the urgent demand for innovative nursing talents and the rapid development of nursing disciplines during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…indicates that China has placed increasing importance on innovative behaviours of nurses in recent years. The ongoing worldwide shortage of nurses and limited medical and health budgets have created a need for hospitals to improve their efficiency, and fostering innovative behaviours in nurses is one way for hospitals to increase the efficiency of their innovation outputs while also being a powerful driver for the development of the nursing discipline(Emiralio glu & Sönmez, 2021;Huang et al, 2021). Despite the pressure of the pandemic, nurses have shown a willingness to innovate and to change their practices.…”
mentioning
confidence: 99%
“…Even though they scored highest on problem-finding abilities, most nurses were only centred between 'Hard to do it' and 'Generally do it'. In addition, the nurses could not use scientific methods to solve practical problems and attached less importance to development of patents that can effectively improve work efficiency (Huang et al, 2021), which, to a certain extent, affected the development of primary medical care. Therefore, there is need for the nurse educators to pay more attention to setting up of study design and data analysis skills in community nursing courses.…”
Section: Discussionmentioning
confidence: 99%